Problems of health sustainability in the context of industrial and innovative development - Omarova, A.T.; Jazykbayeva, B.K.; Orynbassarova, Ye.D.; Bespayeva, R.S.; Geissler, G. (BUKETOV BUSINESS REVIEW, 2018)
The Republic of Kazakhstan has achieved significant economic growth and significant results in the country's socio-economic development. However, the implementation of the Programs for Forced Industrial-Innovative Development, the Business Roadmap 2020 and others within the framework of the traditional production and consumption scheme causes a multiple increase in anthropogenic pressures on the regions, including an increase in the seizures of mineral, hydrocarbon, water, land, energy resources, emissions and volumes of pollutants, the growth of new industries and infrastructures, determining their uneven development and increasing the degree of desertification of territories. To date, a number of environmental problems remain unresolved in Kazakhstan, which require a different approach to the development of state environmental policies and sustainable development management models. Let us cite the main factors hampering the country's sustainable development: inefficient resource management; Excessive consumption of natural resources (anthropogenic impact); commodity orientation of the economy; excessive urbanization of territories; deterioration of public health; human capital; imbalance of regional development; low productivity of economic sectors; increase in the number of industrial zones; deficiency of water resources and desertification of territories; environmental pollution; energy intensity of production; low land productivity and crop yields and other factors. In this article, we will consider in the regional aspect such a factor as the health of the population, taking into account the environmental problems and the environmental situation in the region. The article presents the economic and mathematical model of sustainable development management in the context of the regions of the Republic of Kazakhstan.